(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To synthesize clinical evidence on the effects of herbal medicine on sperm concentration, motility, and morphology in infertile men. Methods: Literature was searched in PubMed/MEDLINE, Scopus, Web of Science, and the Cochrane Library up to October 2025 using keywords related to male infertility, abnormal semen parameters, and herbal medicine. Results: Ashwagandha, Nigella sativa, and Korean red ginseng showed a trend toward improving sperm concentration, motility, and, to some extent, morphology in several clinical studies. Maca produced inconsistent findings, with some studies reporting modest improvement but without clear superiority over placebo. The main proposed mechanisms involved antioxidant effects, regulation of reproductive hormones, and improvement of testicular microcirculation. Overall, herbal interventions were relatively well tolerated, with few serious adverse effects reported. Conclusion: Herbal medicine may help improve certain semen parameters in infertile men; however, the strength of evidence remains limited because of small sample sizes, heterogeneity of herbal preparations, and the lack of data on important clinical outcomes such as pregnancy and live birth rates.